Edukasi Bahaya Konsumsi Mie Instan di Kalangan Mahasiswa Universitas Halu Oleo - Devi Safitri Effendy; Rahayanah Rahayanah; Ananda Ramadani; Ayu Anisa Putri A; Wa Atiqah; Waode Hety Dirahayu; Mirnawati Mirnawati; Nur Nita; Fifi Nirmala; Harleli Harleli; Febriana Muchtar; Hariati Lestari; Hartati Bahar (Pusat Riset dan Inovasi Nasional, 2025)
Instant Noodle Consumption Education Among University Students is a program aimed at raising awareness of the dangers of excessive instant noodle consumption and the importance of a balanced diet. A situational analysis using a questionnaire based on the Health Belief Model (HBM) provided foundational information on students' perceptions of instant noodles, serving as the basis for developing educational media. Next, a combination of poster and educational video media was used to encourage students to limit their instant noodle consumption. Educational content was shared through the social media platform Instagram to reach a larger student audience, leveraging this platform's capacity for rapid and widespread information dissemination. The results showed an increase in students' awareness about balanced nutrition and the health impacts of instant noodles. Ongoing education is expected to help foster healthier eating habits among students.